'Just Say No': public dissent over sexuality education and the Canadian national imaginary. Issue 3 (4th May 2019) - Bialystok, Lauren; Wright, Jessica
ABSTRACT: Scholars of sexuality have argued that 'moral panics' about sexuality often stand in for broader conflicts over nationality and belonging. Canada has spent decades cultivating a national image founded on multiculturalism and democratic equality. The Ontario sexuality education curriculum introduced in 2015 drew audible condemnation from a variety of groups. Drawing from Critical Discourse Analysis and Critical Race Theory, we argue that the public discourse surrounding these protests exposed the limits of Canadian pluralism, fuelling a meta-debate about the 'Canadianness' of recent immigrants and the incompatibility of liberal values with those of non-Westerners, especially Muslims. We explain this in terms of contextual factors such as Ontario's publicly funded Catholic school system and anti-Muslim xenophobia in the post-9/11 era. Our analysis speaks to the importance of intersectional social justice efforts as part of the movement for comprehensive sex education.